Using Digital Texts in Interactive Reading Activities for Children with Language Delays and Disorders: A Review of the Research Literature and Pilot Study - Boyle, Susannah; McCoy, Ashley; McNaughton, David; Light, Janice (Seminars in Speech and Language, 2017)
Participation in interactive reading activities can help children with language delays and disorders build important early language and literacy skills. Digital texts (i.e., books presented on tablets and computers) provide new opportunities for learning and supporting communication. Recently, researchers have investigated the use of digital texts that include visual scene displays (VSDs). In this approach, pictures on a tablet are programmed with “hotspots”; when the picture is touched, a word is spoken aloud. In addition, transition to literacy (T2L) features, including dynamic presentation of the text when a hotspot is activated, can be implemented with VSDs. This article provides a review of interactive reading interventions with children with language delays and disorders, and a discussion of the impact of using digital texts. We also describe the results of a pilot study intervention using digital texts including VSDs and T2L features with children with language delays in an inclusive preschool setting.
Keywords: Language delays; language disorder; interactive reading; young children; augmentative and alternative communication; AAC; digital texts